2021
DOI: 10.1038/s41467-021-27292-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in notifiable infectious disease incidence in China during the COVID-19 pandemic

Abstract: Nationwide nonpharmaceutical interventions (NPIs) have been effective at mitigating the spread of the novel coronavirus disease (COVID-19), but their broad impact on other diseases remains under-investigated. Here we report an ecological analysis comparing the incidence of 31 major notifiable infectious diseases in China in 2020 to the average level during 2014-2019, controlling for temporal phases defined by NPI intensity levels. Respiratory diseases and gastrointestinal or enteroviral diseases declined more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
98
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 24 publications
20
98
1
1
Order By: Relevance
“…These results substantiate prior studies of influenza, RSV and other upper and lower respiratory infections during the winter 2020/2021 season [10,23]. NPIs are believed to have reduced influenza transmission during the 2020/2021 influenza season while also contributing to the decline in mumps and other respiratory infections in some countries [12,2325]. While the decline in influenza could be partially attributed to a decrease in the number of specimens sent for respiratory panel testing, as evidenced by an 61% decrease in US specimens sent for testing in 2020, studies have shown that the positivity rate among specimens sent had also declined, approximately 98%, during winter 2020/2021 [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results substantiate prior studies of influenza, RSV and other upper and lower respiratory infections during the winter 2020/2021 season [10,23]. NPIs are believed to have reduced influenza transmission during the 2020/2021 influenza season while also contributing to the decline in mumps and other respiratory infections in some countries [12,2325]. While the decline in influenza could be partially attributed to a decrease in the number of specimens sent for respiratory panel testing, as evidenced by an 61% decrease in US specimens sent for testing in 2020, studies have shown that the positivity rate among specimens sent had also declined, approximately 98%, during winter 2020/2021 [11].…”
Section: Discussionsupporting
confidence: 91%
“…influenza, acute lower respiratory infections) and otitis media (the main contributor to the “middle ear diagnosis” subchapter) clustered in our analysis given their shared dramatic decrease in IRR during April and May 2020 and their uncharacteristically low relative incidence during fall/winter 2020/2021. These results substantiate prior studies of influenza, RSV and other upper and lower respiratory infections during the winter 2020/2021 season [10,23]. NPIs are believed to have reduced influenza transmission during the 2020/2021 influenza season while also contributing to the decline in mumps and other respiratory infections in some countries [12,2325].…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that the decrease in the HPV infection rate may come from the reduction of new HPV infections. A recent Chinese nationwide research showed that the incidence of STIs was significantly reduced during COVID-19 pandemic ( 16 ). The decrease of the five most prevalent STIs was positively linked with COVID-19 pandemic and strict quarantine measures ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variation is also likely across countries as NPIs used have varied substantially in both timing and stringency [39] . Furthermore, despite short-term reductions in transmission, recent studies have highlighted the risks of resurgence and outbreaks following the relaxation of NPIs [40] , [41] , [42] . Further work and data are required to assess the full effects of these interventions.…”
Section: Discussionmentioning
confidence: 99%